Improving Students Activity and Learning Outcomes by Using Contextual Teaching and Learning Base on Scientific - Aang Hidayatullah (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2016)
The purpose of the research to describe the use of Contextual Teaching And Learning base on Scientific for increasing students activities and to describe the use of Contextual Teaching And Learning base on Scientific for increasing student learning outcome The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VII at MTs Al Ishlah Mayang. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method thet used qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: CTL base on Scientific, students activity, and learning outcome